Client’s Effort in Intervening State’s Financial Audit Result: Grounded-Theory Approach - Muhammad Ikbal (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2020)
This paper draws its conclusions using an inductive approach. We find interesting symptoms in the field related to clients' efforts to influence audit opinion in the public financial audit process in various regions in Indonesia. For the purpose of inductive reasoning, we use a grounded theory approach as a tool for analysis and for drawing conclusions. Our findings are that there are at least seven ways and efforts taken by clients to intervene with the audit decisions made by BPK, and thus we eventually formulate a theory that the audit system in the government requiring interaction between the auditee, in this case the financial management apparatus and the BPK auditor, gives birth to a communication. This communication is used by the auditee to influence the results of the audit. The research implication is that there are ways for auditors to prevent clients from misusing the opportunities to influence audit result.